2015
DOI: 10.1186/s12348-015-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral endogenous endophthalmitis caused by vancomycin-resistant Staphylococcus epidermidis in a neonate

Abstract: BackgroundNeonatal bilateral endogenous endophthalmitis is rare and often results in devastating visual outcome.FindingsAn 18-day-old neonate presented with whitening of the cornea in the left eye. The child was examined under anesthesia, and a diagnosis of bilateral endogenous endophthalmitis was made. Vitreous biopsy from the left eye showed no growth. Blood samples showed growth of Staphylococcus epidermidis which was multidrug resistant (including vancomycin) but sensitive to piperacillin-tazobactam. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, sampling the vitreous might be difficult and, even if a sample could be obtained, several days would be needed to obtain the details of the bacteria detected and to confirm antibiotic sensitivities. Furthermore, endogenous endophthalmitis caused by vancomycin resistant bacteria has also been reported [1,2]. Thus, we consider IVI of 1.25% / 0.1 ml PI to be a potential treatment option, to be administered in selected cases, instead of IVI of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sampling the vitreous might be difficult and, even if a sample could be obtained, several days would be needed to obtain the details of the bacteria detected and to confirm antibiotic sensitivities. Furthermore, endogenous endophthalmitis caused by vancomycin resistant bacteria has also been reported [1,2]. Thus, we consider IVI of 1.25% / 0.1 ml PI to be a potential treatment option, to be administered in selected cases, instead of IVI of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a broad range of causative organisms including both bacterial and fungal species. Recently, multidrug-resistant bacteria and vancomycin resistant bacteria have also been reported in endogenous endophthalmitis [1,2]. In addition, vancomycin-associated hemorrhagic occulusive retinal vasculitis was reported following prophylactic use of an intracameral injection for cataract surgery [3].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the Endophthalmitis Vitrectomy Study showed that 68% of culture-positive isolates were coagulase-negative Staphylococcus [ 1 ]. However, Staphylococcus epidermidis is also known to be the predominant microbe in traumatic endophthalmitis and is listed among the organisms causing endogenous endophthalmitis [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like systemic infections, recent reports suggest that ∼50% of ocular S. aureus isolates from keratitis/endophthalmitis are methicillin-resistant (MRSA) and they often cause aggressive infections leading to significant vision loss ( Callegan et al., 2007 ; Bispo et al., 2015 ; Pachigolla et al., 2007 ; Kolar and McDermott, 2011 ; Hernandez-Camarena et al., 2015 ; Hsiao et al., 2012 ; Deramo et al., 2008 ). Additionally, vancomycin-resistant SA endophthalmitis has also emerged as post-surgical complication in recent years leading to poor visual outcomes ( Pathengay et al., 2011 ; Das et al., 2011 ; Relhan et al., 2015 ; Stroh, 2012 ; Gupta et al., 2011 ). The situation is further compounded by the fact that staphylococcal infections are challenging to eradicate owing to their ability to make biofilms on intraocular or contact lenses, which impede both the penetration of antibiotics and the infiltration of immune cells ( Bispo et al., 2015 ; McCarthy et al., 2015 ; Talreja et al., 2014a , 2014b ).…”
Section: Introductionmentioning
confidence: 99%